Win-win in distributive negotiations: The economic and relational benefits of strategic offer framing - SCHAERER, Michael (Institutional Knowledge at Singapore Management University, 2020)
In distributive negotiations, people often feel that they have to choose between maximizing their economic outcomes (claiming more value) or improving their relational outcomes (having a satisfied opponent). The present research proposes a conversational strategy that can help negotiators achieve both. Specifically, we show that using an offer framing strategy that shifts offer recipients’ attention to their reservation price (e.g., “How does my offer compare to your minimum price?”) leads to both (a) an assimilation effect whereby recipients make more favorable counteroffers (economic benefit) as well as (b) a contrast effect whereby recipients feel more satisfied with the negotiation (relational benefit). We find evidence for the effectiveness of this conversational strategy across four experiments (N=1,522) involving different negotiation contexts (real estate, restaurant sale) and participant samples (MBAs, sales agents, online participants), and also document negotiator power as an important boundary condition. Overall, our research suggests that economic and relational benefits do not have to be mutually exclusive in distributive negotiations, that the perceived extremity of an offer is subjective and can be strategically influenced, and that assimilation and contrast effects can operate simultaneously when they relate to separate outcomes.